2007
DOI: 10.2298/bah0701357t
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic characteristics of growth and carcass traits of Lori-Bakhtiari sheep

Abstract: Abstract:In this study, direct and maternal heritabilities were estimated for growth traits and carcass characteristics in Lori-Bakhtiari sheep. Data for birth weight (BW; n=5826), weaning weight (WW; n=5408), body weight at six months of age (6MW; n=4237), body weight at slaughter (SW; n=396), cold carcass weight (CCW; n=291), lean weight (LW; n=204), bone weight (WB; n=291), fat weight (WF; n=204) and fat-tail weight (FTW; n=396) were used to estimate the heritabilities. The data for first three traits had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The range of direct heritability estimates for birth weight from multivariate analysis in the literature varies substantially from 0.04 in Romanov and Kermani breeds (Maria et al 1993;Rashidi et al 2008) to 0.46 in Menz breed (Gizaw et al 2007). Talebi et al (2007) reported that estimates of heritability for LBW and LWW of Lori-Bakhtiari sheep were 0.30±0.03 and 0.13±0.03 direct and 0.22 and 0.17 maternal, respectively. Consequently, genetic progress is possible for growth traits by selection.…”
Section: Variance Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of direct heritability estimates for birth weight from multivariate analysis in the literature varies substantially from 0.04 in Romanov and Kermani breeds (Maria et al 1993;Rashidi et al 2008) to 0.46 in Menz breed (Gizaw et al 2007). Talebi et al (2007) reported that estimates of heritability for LBW and LWW of Lori-Bakhtiari sheep were 0.30±0.03 and 0.13±0.03 direct and 0.22 and 0.17 maternal, respectively. Consequently, genetic progress is possible for growth traits by selection.…”
Section: Variance Componentsmentioning
confidence: 99%
“…It is essential to have knowledge of genetic parameters for these economically important criteria to formulate breeding strategies for better production (Gowane et al 2015). The relative importance of direct and maternal additive genetic effects for growth should be considered when sheep producers formulate their breeding plans (Talebi et al 2007). Maternal genetic effects arise from allelic differences between individual mothers at loci influencing offspring phenotype and are a heritable component of phenotypic variance themselves.…”
Section: Introductionmentioning
confidence: 99%